2010
DOI: 10.1093/brain/awq075
|View full text |Cite
|
Sign up to set email alerts
|

Divergent network connectivity changes in behavioural variant frontotemporal dementia and Alzheimer’s disease

Abstract: Resting-state or intrinsic connectivity network functional magnetic resonance imaging provides a new tool for mapping large-scale neural network function and dysfunction. Recently, we showed that behavioural variant frontotemporal dementia and Alzheimer's disease cause atrophy within two major networks, an anterior 'Salience Network' (atrophied in behavioural variant frontotemporal dementia) and a posterior 'Default Mode Network' (atrophied in Alzheimer's disease). These networks exhibit an anti-correlated rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

113
887
13
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 899 publications
(1,017 citation statements)
references
References 96 publications
113
887
13
4
Order By: Relevance
“…Different types of properties, such as local spontaneous activity (ReHo), local network (DMN and/or its anti-correlated network), and whole brain network, derived from SLFF have been taken as features to discriminate patients from normal controls (Table 4). In general, both the sensitivity and specificity of these studies has been above 80% (Greicius et al 2004;Song et al 2006;Wang et al 2006a;Calhoun et al 2008a;Shi et al 2007;Shen et al 2010;Zhou et al 2010), suggesting that the activity patterns of SLFF have the potential to become brain imaging biomarkers to improve the sensitivity and specificity of the current clinical diagnosis of neuropsychiatric disorders. And compared to task-related fMRI, the SLFF within the resting-state network may be more effective at identifying functional pathology associated with AD risk (Fleisher et al 2009).…”
Section: Pilot Studies Of Slff As a Brain Imaging Biomarkermentioning
confidence: 99%
“…Different types of properties, such as local spontaneous activity (ReHo), local network (DMN and/or its anti-correlated network), and whole brain network, derived from SLFF have been taken as features to discriminate patients from normal controls (Table 4). In general, both the sensitivity and specificity of these studies has been above 80% (Greicius et al 2004;Song et al 2006;Wang et al 2006a;Calhoun et al 2008a;Shi et al 2007;Shen et al 2010;Zhou et al 2010), suggesting that the activity patterns of SLFF have the potential to become brain imaging biomarkers to improve the sensitivity and specificity of the current clinical diagnosis of neuropsychiatric disorders. And compared to task-related fMRI, the SLFF within the resting-state network may be more effective at identifying functional pathology associated with AD risk (Fleisher et al 2009).…”
Section: Pilot Studies Of Slff As a Brain Imaging Biomarkermentioning
confidence: 99%
“…Individuals with MCI who have comorbid emotional complaints are more likely to progress to dementia than those without such symptoms (9)(10)(11)(12)(13). Taken together, these studies suggest that a clinical presentation that includes both cognitive decline and emotion dysregulation may point to an underlying AD process and that emotional symptoms themselves may portend or even exacerbate disease progression (9,11,14).…”
mentioning
confidence: 92%
“…Individuals with MCI who have comorbid emotional complaints are more likely to progress to dementia than those without such symptoms (9-13). Taken together, these studies suggest that a clinical presentation that includes both cognitive decline and emotion dysregulation may point to an underlying AD process and that emotional symptoms themselves may portend or even exacerbate disease progression (9,11,14).The medial temporal lobe is among the earliest sites of disease in MCI and AD (2, 15), and hippocampal atrophy is associated with worse episodic memory performance on standardized neuropsychological testing (16) and predicts conversion from MCI to AD (17). Similarly, functional imaging studies reveal diminished intrinsic connectivity, the degree to which distributed brain structures fluctuate in synchrony in the absence of a structured task, in the default mode network in MCI and AD (18,19).…”
mentioning
confidence: 99%
“…In addition, an emerging view suggests that cognitive performance in general might rely on the dynamic interaction between the DMN and two other large-scale neural networks: the fronto-parietal task-positive network (FPN), which is associated with attention and cognitive control, and the salience network (SN) in anterior cingulate and fronto-insular cortex, which is involved in the selection of emotionally and motivationally relevant stimuli (Andrews-Hanna et al, 2014;Chen et al, 2013;Fox et al, 2005;Seeley et al, 2007;Sridharan et al, 2008;Spreng et al, 2013). These three neural networks are central to cognition, as they are engaged in a large number of functions, and their disruption has been associated with a variety of clinical syndromes, such as schizophrenia, traumatic brain injury, and Alzheimer's disease (Manoliu et al, 2014;Sharp et al, 2014;Zhou et al, 2010). In addition, evidence suggests that the disruption of the dynamic coordination of these large-scale networks constitutes one of the main causes of cognitive decline associated with ageing (Andrews-Hanna et al, 2007;Sambataro et al, 2010), as shown by reduced neural activity in the DMN and SN at rest (Allen et al, 2011;Onoda et al, 2012) and RESTING STATE NETWORKS IN THE AGEING BRAIN 4 increased activity in the FPN of older adults during visual tasks .…”
Section: Introductionmentioning
confidence: 99%